Information and credit cycles: Causes and consequences of financial instability - Aino Silvo (Bank of Finland, 2018)
This thesis consists of an introductory chapter and three self-contained essays that apply insights from the microeconomic theory of corporate finance in a macroeconomic setting in order to explain and understand various market failures that were at the roots of the global financial crisis of 2007–2009. In particular, I study various forms of incomplete information in the credit market, and their implications on financial stability and on business cycles in the aggregate economy. I also seek to understand how monetary and macroprudential policies can be used to maintain financial stability, and how these two policies interact.
URN:NBN:fi:bof-201805311590
Keywords: 330; Subprime-Krise; Kreditmarkt; Wohnungsmarkt; Unvollkommene Information; Marktversagen; Geldpolitik; Finanzmarktaufsicht; USA